ANALYSIS OF RISK FACTORS IN PATIENTS WITH CHRONIC KIDNEY FAILURE AT BAHTERAMAS HOSPITAL - Budiarti, Gusti Ayu Kade; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT Chronic kidney failure (CKD) is a disease that can cause death. This disease is a disease caused by a decrease in kidney function so that the metabolic balance of fluids in the body is disrupted. Hemodialysis is one of the therapies most commonly used by chronic kidney failure patients to maintain kidney function. Indonesia is a developing country where many cases of chronic diseases are found which lead to death. One of these chronic diseases is chronic kidney disease, this disease experiences an increase in the number of patients every year so that it becomes one of the factors of death in the world. The aim of this study is to determine the most common risk factors that occur in CKD patients at Bahteramas RSU in 2021-2022 who are undergoing hemodialysis therapy. This research uses a quantitative study with a case control design. The results of the study showed that primary glomerulopathy was caused by 1.7%, diabetes mellitus in 10%, hypertension in 84.1%, polycystic kidney and gout neuropathy in 0.9%, and other causes in 2.1%. Based on these results, it can be concluded that the largest risk factor is the presence of hypertension in 345 cases with a percentage of 84.1%. Hemodialysis therapy carried out by patients can have bad effects if there is a lack of knowledge about this therapy. So it is necessary to carry out health promotion for chronic kidney failure patients with hemodialysis therapy. Keywords: chronic kidney failure, hemodialysis, risk factors